Relação entre Percepção e Comportamento de risco e níveis de habilidades cognitivas em um grupo de adolescentes em situação de vulnerabilidade social - Paulino, Janaina Aparecida (2009)
The aim ob this study was to analyze the relationship between cognitive abilities level (verbal and non verbal intelligence) risk perception and intention to show risk behavior in a teenagers group in social vulnerability situation. The main hypothesis was that cognitive abilities high levels would shoe greater risk perception and would be less engaged in risk behavior. Forty-eight teenagers of a social group named Young Agent were studied in a city in Triângulo Mineiro, a region of Minas Gerais State, Brazil. They were 15-17 years old teenagers whose families experience social risk situation according to Brazilian Social Assistance Unified System (SAUS). The subjects answered three instruments: a risk perception and intention to show risk behavior scale and two cognitive ability tests Reasoning Test Battery (BPR-5) and Raven s progressive matrix test. These instruments were applied in a Social Assistance Reference Center after voluntary accepting and parents permission. Data had descriptive and correlative analysis. The results showed that, in a general way, the sample showed average performance in a range in cognitive tests. Men showed significant better performance in mechanic reasoning than women. Concerning to risk perception types there was only a moderate positive relation between ethic and legal risk perception and health one. Verbal reasoning related to ethic and health risk perception. Among less-schooling participants higher was ethic and legal risk perception higher were also health and social risk perception.. Mechanic reasoning was related to intention to show ethic and legal as well to finance risk behavior. There was no significant sexual difference when analyzing risk perception and risk behavior. This search allowed to verify some relation between risk perception and intelligence as well it presented relation between the types of intention to engage to risk behavior and intelligence. These data somehow confirm our initial hypothesis that there is a relationship between intelligence and risk perception. It was possible to see that higher intellectual abilities help to perceive these kind of risk, but it does not grantee avoiding behavior which could generate consequent sanctions and punishments. Studies like this have social and theoretical relevance to preventive social programs directed to teenagers in risk.